2011
DOI: 10.12927/hcpol.2011.22179
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Home Care Expenditures and Death at Home for Cancer Patients in an Integrated Comprehensive Palliative Home Care Pilot Program

Abstract: Facteurs de prévision des dépenses pour les soins à domicile et les décès à domicile chez les patients atteints du cancer dans le cadre d'un programme pilote de soins palliatifs complets à domicile

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…Current literature notes that the presence of certain clinical factors, such as a hematological tumour (9,38) or the need for greater pain and symptom control, decrease one's likelihood of dying in one's preferred place (7). Social factors, such as medical costs and the burden placed on others, were cited as indicators of equitable access to palliative care services (8,39,40). For instance, some patients cannot afford even small out-of-pocket costs for palliative care services, and the availability of informal caregivers can vary.…”
Section: Discussionmentioning
confidence: 99%
“…Current literature notes that the presence of certain clinical factors, such as a hematological tumour (9,38) or the need for greater pain and symptom control, decrease one's likelihood of dying in one's preferred place (7). Social factors, such as medical costs and the burden placed on others, were cited as indicators of equitable access to palliative care services (8,39,40). For instance, some patients cannot afford even small out-of-pocket costs for palliative care services, and the availability of informal caregivers can vary.…”
Section: Discussionmentioning
confidence: 99%
“…Access to care in the home has also been associated with home death. Previous studies investigating the availability and utilization of home care and home visits found that patients were more likely to die at home or out of acute care if they lived in an area with more home hospice providers [ 10 ], received home care in the last 6 months of life [ 15 ], or received more nursing and personal support worker visits [ 6 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Forward planning using instruments to measure functional status, combined with as needed home visits to pre‐empt crises provided a solid platform on which to deliver quality community palliative care. Better care coordination has been demonstrated to improve rates of home death in the international setting …”
Section: Discussionmentioning
confidence: 99%
“…The National Health and Hospitals Reform Commission recommends ‘ integrating multi‐disciplinary primary health care services…better coordination and continuity of care… [and] strengthening consumer…empowerment ’ . High‐quality end‐of‐life care involves managing multiple co‐morbidities, symptom control and ‘psychological, social, loss/grief, practical and end‐of‐life preparation’ . Strategies include:…”
Section: Introductionmentioning
confidence: 99%